Understanding Students’ Positive Emotions Through Photovoice Study - Ahmad Muhammad Diponegoro; Agungbudiprabowo Agungbudiprabowo; Siti Muyana; Dian Ari Widyastuti (Universitas Ahmad Dahlan, 2020)
The purpose of this study was to explore the use of the photovoice methodology to understand students' positive emotion related to their daily activities. Photovoice is an innovative method of participatory action research that enables individuals and communities to use photography and writing to solve various problems. This study included a qualitative analysis of 42 photovoice papers prepared by 15 Guidance and Counseling students The images and thematic analysis reveal the following main themes: religion, learning activities and places and leisure. This study provides evidence that photovoice is a promising method for understanding positive psychological variables of undergraduateÂ students as a tool for personal empowerment and transformation.